Giving Tshuve to the sick: correspondence columns of the Yiddish medical press in Poland. Issue 1 (24th May 2019) - Tuszewicki, Marek
Argument: Several Yiddish medical publications of various profiles appeared in independent Poland until 1939. These print media were associated with OZE and TOZ organizational structures and aimed to promote modern concepts of health and healthcare among the Jewish population in its native tongue. Some of these magazines offered space for direct consultations, which took the form of a correspondence corner. Questions sent in by readers ranged from apparently neutral topics, such as a healthy diet or hygiene, to controversial matters tormenting individuals in provincial milieus. The correspondence gives us an insight into popular ways of thinking about health and disease and indicates issues of high importance for a society in the process of modernization. The present paper discusses the questions and answers as they appeared in the Yiddish medical press (particularly in the Folksgezunt and Der Doktor ), and presents the most crucial aspects of Jewish life they shed light on, including the historical and cultural background.